Breeding biology of long-tailed cinclodes cinclodes pabsti sick, 1969 (Passeriformes: Furnariidae) - Zocche, Jairo José; Carvalho, Fernando; Cruz-Neto, Ariovaldo Pereira [UNESP] (Universidade de São Paulo. Agência de Bibliotecas e Coleções Digitais, 2021)
Cinclodes pabsti is an endemic passerine restricted to the highland areas in southern Brazil. The aim of this study was to provide information on its breeding biology. The nesting cavities along road cuts were monitored from May 2008 to March 2011. The survey was carried out monthly from May to July 2008, February to July 2009, 2010 (non-breeding season), weekly from August 2008 to January 2009, 2010 (breeding season), and on a 2 to 4-days basis from August 2010 to January 2011. The geographic location, physical characteristics, and soil/substrate type in which the nesting cavities were situated were recorded. The total number of cavities used in the three breeding seasons was 136, resulting in 295 nests. The distance of a nest to its nearest neighbor ranged from 24-2,368 m, with a higher number of nests (n = 34; 59.7%) in the distance interval of 24-500 m. There was a greater usage of cavities located in Inceptisols, and the distances of nesting cavity entrances to the ground and to the top of road cuts were 1.6 ± 0.9 m and 0.8 ± 0.62 m, respectively. The breeding season lasted 148 days from mid-August to early January. Clutch size (n = 256) varied from 2 to 3 eggs, and the eggs (n = 155) had a total length of 27.2 ± 1.3 mm, breadth of 20.9 ± 0.8 mm, and mass of 6.2 ± 0.7 g. The incubation phase lasted 17.3 ± 0.8 days and the nestling phase for 18.3 ± 1.5 days. The body mass of the chicks was 6.0 ± 1.0 g just after hatching and reached a maximum of 59.6 ± 2.4 g at 16 days of age. Our results can contribute to filling the gaps in knowledge of C. pabsti ecology, because its habitat is under high anthropic pressures and the information on its life history is yet limited.
Keywords: Breeding phenology; Cavity nesting; Highland grasslands; Parental care; Southern Brazil